2015
DOI: 10.17795/nmsjournal25922
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Active and Passive Intradialytic Pedaling Exercises on Dialysis Efficacy, Electrolytes, Hemoglobin, Hematocrit, Blood Pressure and Health-Related Quality of Life

Abstract: Background:The effect of exercise during hemodialysis has been a controversial issue, however, there are just few studies about the effect of active exercise during hemodialysis. Objectives: This study aimed to compare the effects of passive and active intradialytic pedaling exercises on dialysis efficacy, electrolytes, hemoglobin, hematocrit, blood pressure and health-related quality of life in hemodialysis patients. Patients and Methods: This quasi-experimental study was conducted on 16 hemodialysis patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 10 publications
3
45
1
11
Order By: Relevance
“…Five of seven studies showed a statistically significant result or a large effect size for increased potassium clearance and/or reduced serum concentrations with intradialytic exercise.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Five of seven studies showed a statistically significant result or a large effect size for increased potassium clearance and/or reduced serum concentrations with intradialytic exercise.…”
Section: Resultsmentioning
confidence: 95%
“…One acute study implemented a randomized controlled design . Four of the intervention studies performed a randomized controlled trial, one study utilized a within subject crossover design, and two studies observed pre and post changes in an intervention group without a control comparison arm (1 group intervention) ).…”
Section: Resultsmentioning
confidence: 99%
“…Intradialytic exercise can obtain higher adherence rates than interdialytic exercise, particularly if supported by exercise professionals . Literature in the field of renal rehabilitation recommends exercise implementation in the first part of the HD session to avoid hemodynamic instability. To test this theory, Parsons et al exercised through to the third hour of dialysis.…”
Section: Virtual Reality Exercise: At the Beginning Or End Of Dialysis?mentioning
confidence: 99%
“…In 2005, Caner reported the lack of any effect of PE on the rebounds of urea, potassium, or creatinine, nor on urea clearance. Similarly, and more recently, Orcy (2014, Brazil) and Musavian (2015, Iran) have informed that there were no changes with ID PE.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that ID PE has no effect when practiced during the first two session hours on dialysis dose and postdialysis rebound. Thus our results support those reported by Caner , Orcy , and Musavian .…”
Section: Discussionmentioning
confidence: 99%